Public Health Informatics: The Importance of COVID-19 Dashboard in KSA : Health Information Sharing and Visualization - Anas Ali Alhur (The Indonesian Institute of Science and Technology Research, 2023)
The use of technology is enabling businesses, individuals, and governments to combat COVID-19. Containing and measuring global concerns such as Coronavirus will require critically assessing technological developments. This paper evaluates the COVID-19 dashboard developed by the Saudi Ministry of Health (MOH). A scoping review of published and unpublished documents was conducted. The Saudi Arabia MOH provides figures, graphs, and statistics. The researcher found that clicking one button allows access to critical information, enabling individuals to understand how the disease spreads around the country. The Saudi MOH's COVID-19 dashboard provided accurate, reliable, and current information. COVID-19 information is effectively communicated through technology. With the help of data visualization, many citizens can better understand COVID-19. Given their dynamic nature, the evolution of COVID-19 dashboards over time is crucial. A broader range of indicators may assist in better monitoring the impact of COVID-19 on the economy and society. During this crisis, dashboards must include features that facilitate their use by people with disabilities.